POTENTIAL ANALYSIS AND DEVELOPMENT STRATEGY OF GAMBIR JASMINE COMMODITY IN RAKIT SUBDISTRICT BANJARNEGARA REGENCY - Sarno -; Eko Apriliyanto (Universitas Muhammadiyah Semarang, 2014)
Gambir Jasmineis one of the unique and rare commodities, it is only found in the RakitSubdistrict Banjarnegara Regency. The difference potential of each village in producing jasminegambir commodity causes differences in the distribution ofthe commodities its produces.Itmeans that there is a gambir jasmine commodities evenly distributed in each village, and thereare concentrated in one village. Needed research about potential and distribution analysis,development and implementation strategy of commodity growth centers gambir jasmine andpotential area of its development so that commodities of gambir jasmine can be supreme andmainstay commodity in Rakit District Banjarnegara Regency.The aim of this research is toanalyze the potential of gambir jasmine as a mainstay commodity on each village, determinecommodity distribution and development strategy of gambir jasmine areas in Rakitsubdistrict.This research was conducted by using survey method with main target is all farmerof gambir jasmine in Rakit District. The data analysis used Location Quotient, Shift Analysis(SA), Super Impose.The result shows that all villages in Rakit District have potential fordevelopment gambir jasmine as mainstay commodity. Development strategy of gambir jasminein Rakit Subdistrict uses SWOT analysis. Based on SWOT analysis so that analysis producedgambier jasmine development strategies in Rakit. Key word: Potential, Commodity, Strategy, Banjarnegara